Akar Teori Konflik - Mohammad Dzofir (AL-BURHAN, 2017)
This paper will describe the origins of the birth of conflict theory by describing the theory and thinking of the founding fathers of conflict theory. Furthermore, to clarify the position of conflict theory, this paper will compare in contrast the perspective of conflict theory. Conflict theory is the antithesis of the theories constructed by functional groups an has a very sharp distinction with functional theory. Structualisme in the tradition of conflict.on the theory of structural functionalism in the tradition of conflict. On the theory of stuctural functionalism emphasized is integration, value equation, and social stability. While the structural conflict is empasized is integration, value equation, and social stability. While the structural conflict is empasized precisely the opposition, super ordination and subordination relationships, power differences and social change.